2022
DOI: 10.1021/acs.jpca.2c01261
|View full text |Cite
|
Sign up to set email alerts
|

From Molecules with a Planar Tetracoordinate Carbon to an Astronomically Known C5H2 Carbene

Abstract: Ethynylcyclopropenylidene ( 2 ), an isomer of C 5 H 2 , is a known molecule in the laboratory and has recently been identified in Taurus Molecular Cloud-1 (TMC-1). Using high-level coupled-cluster methods up to the CCSDT(Q)/CBS level of theory, it is shown that two isomers of C 5 H 2 with a planar tetracoordinate carbon (ptC) atom, (SP-4)-spiro[2.2]pent-1,4-dien-1,4-diyl ( 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 90 publications
3
17
0
Order By: Relevance
“…However, some small PAH-like molecules, like isomers of C 5 H 2 , have a lower symmetry which can allow for a nonzero dipole moment and possible rotational activity. Recently, two isomers of C 5 H 2 , l-C 5 H 2 and ethynyl cyclopropenylidene (c-C 3 HC 2 H), have been independently detected in Taurus Molecular Cloud-1 and pathways of formation have been determined experimentally and supported theoretically (He et al, 2020;Cabezas et al, 2021;Cernicharo et al, 2021;Karton and Thimmakondu, 2022). The detection of C 5 H 2 isomers could allude to other rotationally dark PAHs lurking in the interstellar medium.…”
Section: Introductionmentioning
confidence: 87%
“…However, some small PAH-like molecules, like isomers of C 5 H 2 , have a lower symmetry which can allow for a nonzero dipole moment and possible rotational activity. Recently, two isomers of C 5 H 2 , l-C 5 H 2 and ethynyl cyclopropenylidene (c-C 3 HC 2 H), have been independently detected in Taurus Molecular Cloud-1 and pathways of formation have been determined experimentally and supported theoretically (He et al, 2020;Cabezas et al, 2021;Cernicharo et al, 2021;Karton and Thimmakondu, 2022). The detection of C 5 H 2 isomers could allude to other rotationally dark PAHs lurking in the interstellar medium.…”
Section: Introductionmentioning
confidence: 87%
“…The plausibility of an ethynyl-functionalized c-C 3 H 2 derivative was first hypothesized by Vrtilek et al (1987) and computationally validated by Cooper & Murphy (1988) before being detected in the laboratory by Travers et al (1997). The structural isomers of c-C 3 HC 2 H have also been studied in detail, showing that this form is the lowest in energy for the singlet spin multiplicity (Seburg et al 1997;Karton & Thimmakondu 2022). Following the astrophysical detection of c-C 3 HC 2 H (Cernicharo et al 2021), a mechanistic study of its formation found that c-C 3 HC 2 H may form through a gas-phase reaction between c-C 3 H 2 and the ethynyl radical (Fortenberry 2021).…”
Section: Introductionmentioning
confidence: 94%
“…The obtained new structure is optimized at the DFT level without any geometrical constraints. The above intuitive generation is also essential to arrive at the correct PGM geometries [37,38].…”
Section: Structural Of So 3 -(H 2 O)n (N = 1-7) Clustersmentioning
confidence: 99%